Dermal white adipose tissue: A new modulator in wound healing and regeneration - Wu, Zhongyu; Wang, Zhanqi; Chen, Tao; Wang, Dongyang; Zhou, Feng; Zhang, Guorui; Wei, Shan; Wu, Yingying (Regenerative therapy, 2025)
Dermal white adipose tissue (dWAT), distinguished by its origin from cells within the dermis and independence from subcutaneous fat tissue, has garnered significant attention for its non-metabolic functions. Characterized by strong communication with other components of the skin, dWAT mediates the proliferation and recruitment of various cell types by releasing adipogenic and inflammatory factors. Here, we focus on the modulatory role of dWAT at different stages during wound healing, highlighting its ability to mediate the adipocyte-to-myofibroblast transition which plays a pivotal role in the physiology and pathology processes of skin fibrosis, scarring, and aging. This review highlights the regulatory potential of dWAT in modulating wound healing processes and presents it as a target for developing therapeutic strategies aimed at reducing scarring and enhancing regenerative outcomes in skin-related disorders.